Landsjö 2015 - Images and finds list - Rundkvist, Martin; Umeå University (Umeå University, 2016)
Archaeological investigations conducted during July 2015 in Landsjö, Kimstad Parish, Östergötland demonstrated that the steep outer bailey at Landsjö has never been a defensible structure, but was either never finished or never intended to offer anything more than an imposing facade to the west.

The investigations also revealed rich artefact finds within the castle bailey's perimeter. Trenches were opened within two buildings abutting the western wall, and a sandy mount across the dry moat south of the castle was also investigated. The latter seems to be composed entirely of spoil from the digging of the moat, and yielded knapped quartz and two sherds of prehistoric pottery.

The probable home of an 18th century smallholding was also discovered. Four trenches on the castle islet also revealed 25 medieval potsherds, with a majority of Early Red glazed ware Sw. äldre rödgods, dating to the period c. 1250-1350. The few sherds of other wares also fit nicely in this interval. The pottery’s dates agree both with the written sources for Landsjö and with the dates of the six coins found during the excavations.

The dissemination folder includes 258 images of the archaeological investigation, a csv file documenting these images, and an excavation report in pdf format.

Arkeologiska undersökningar (2015) i Landsjö, Kimstad socken, Östergötland, bevisade att Landsjöborgen har aldrig varit en försvarbar struktur. Undersökningarna avslöjade artefaktfynd inuti ringmuren, samtidigt som två byggnader intill västra muren och en dumphög undersöktes. Inom högen hittades två förhistoriska skärvor samt slagen kvarts.

Möjliga spår av 1700-tals torp upptäcktes på holmen, samt 25 medeltida skärvor från fyra schakt, till en större del äldre rödgods (ca. 1250-1350 e.K.)

Mappen innehåller 258 JPG bilder, en CSV-fil med dokumentation på bilderna, samt utgrävningsrapporten i PDF-format.
Landsjö 2015 - Bilder och fyndlista
Excavations in 2015 at Landsjö Castle in Kimstad Parish, Östergötland, Sweden.
Keywords: ceramics; keramik; Neolithic; neolitikum; Middle Neolithic; mellanneolitikum; Middle Ages; medeltid; 18th century; 1700-tal; HISTORY; HISTORIA; History and Archaeology; Historia och arkeologi; Archaeology; Arkeologi